Chapter Lavoro, professione e ozio nei manuali per la confessione della prima età moderna (XVI-XVII sec.) - Zampieri, Giovanni (Firenze University Press, 2025)
Between the 16th and the 17th centuries, the production of literature on Sacramental Penance rose. Targeted to priests and penitents, manuals for confession were among the Catholic Church’s strategies to discipline its members and believers. The professional activities of penitents have been one of the dimensions on which the authors of these texts produced interpretive categories that could be used during confessions. Inspecting these sources, this chapter shows some of the research paths through which the entanglement between the ideas of labor and leisure and the religious life in the early modern Italian peninsula can be reconstructed. Having framed this literature, I show how these texts regulated work activities during the Holy days, spread representations of the sins made by professional estates, and circulated a discourse stigmatizing laziness.